Application of Rare Earth Modification High Tensile Steel on Casting Chain Link - Chen Yuanxiu; Zhou Zhiqiang; Wang Xiaolong (Jixie chuandong)
A kind of rare earth modification high tensile steel which is used for casting chain link is proposed. The composition design,metallographic structure and material processing of this material are studied.The result of the study shows that,this material which formed by composite effective of rare earth modification and heat treatment possesses properties of high strength casting steel,can be used as a substituted material for casting chain link.